Development of Project Based Learning-Based Interactive E-Modules on Industry Standard Front-End Web Development Skills for Vocational High School Students - Bambang Sujatmiko; Dava Daviar Saputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
Codenesa is an electronic module based in which there are interactive features for students to be able to practice the syntaxes explained in this platform. The research has the purpose to create and develop the Codenesa platform which to help support and create senior high vocational students to have a real portfolio as a professional to debut in the digital industry. The flow of the creation and development of Codenesa is through problem finding, data collection, production, and development of the Codenesa platform itself, the validation stage from expert lecturers covering the material and product aspects of Codenesa as a platform. The results of the expert lecturer validation stage show a value of 86.66% while the value of student responses when using the Codenesa platform as a learning medium shows a result of 93.13%. in addition, the increase in results is no less important when the pretest and posttest show significant results. This can be seen from the average pretest of students with a score of 50 and getting an average post-test score of 81.94. It can be concluded that using the Codenesa platform can increase the average value by 31.94% compared to students who study without using Codenesa who can only increase the average value by 13.66%.